ANALISIS KINERJA INSTANSI POLRES SOLOK KOTA SEBAGAI PILOT PROJECT DALAM MERAIH WILAYAH BEBAS BERSIH MELAYANI (WBBM) TAHUN 2019 - Bobi Rizki Ananda; Roni Ekha Putera; Ria Ariany (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
This study aims to describe and analyze what has been done by the Solok City Police as a Pilot Project in the implementation of public services within government agencies in West Sumatra Province. This is because the Solok City Police Station as the only police station that has received the best service award in West Sumatra, then added by the end of 2019 the Solok City Police Station again won the highest predicate in an agency given by Keempan RB as a Free Area for Clean Serving (WBBM) . This study uses qualitative research methods with data collection techniques through interviews, observation and documentation. The informants came from the Solok City Police, the Sector Police and the community in the Solok City Police area. The results of this study indicate that the performance of the Solok City Police Station has exceeded the targets made previously with the realization of performance almost reaching 100%.